Pendampingan Pokdarwis Pembuatan Peta Wisata Di Kelurahan Kranggan Kota Mojokerto - Achmad Risdiyanto; Ilmia Putri Hariyono; Juan Dwi Saputra; Miftakhul Fitriyah; Miftakhul Mufidah; Nindy Pramudita; Riqlatus Sitta Wahyu (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
Pokdarwis (tourism awareness group) is an institution founded by villagers whose members consist of local people who have concern and responsibility and act as a driving force to create a conducive environment and atmosphere for the development of tourism in the village area and to realize sapta charm (trustworthy, orderly, clean, cool, beautiful, friendly, memorable). One of them is the “SEJAHTERA” Pokdarwis which is located in Kranggan Village, Mojokerto City. Pokdarwis SEJAHTERA has a variety of excellent tours, for example